Komparatif Performance Model Keamanan Menggunakan Metode Algoritma AES 256 bit dan RSA - Nizirwan Anwar; Munawwar Munawwar; Muhammad Abduh; Nugroho Budhi Santosa (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Along with the rapid development of information technology, the ability to access and provide information to users is getting quicker and more accurate, Therefore, protecting those from any unauthorized access is very important. Cryptography can be use as they’re one of the fields of information technology development to secure data or messages that are personal and confidential. So, it takes a security to prevent things that are not desired. In this case, the message sending process will be encrypted (plaintext to ciphertext) and the recipient of the message will need to be decrypted (ciphertext to plaintext). The algorithm that we will be using are 256-bit American Encryption Standard (AES) symmetric encryption and RSA asymmetric encryption. Performance testing (size and time-process), integrity ("data integrity"), confidentiality, and "non-repudiation" of data or message security with the algorithm method above will refer to 4 (four) modern cryptographic objectives developed. Those algorithm will be used to encode data stored in document files and implementing it using Python 3.0 language and some support applications. And the results of the process of designing and testing data (text and images) obtained did not experience significant growth, but the encryption / decryption of the RSA algorithm method is much slower than the performance of the AES algorithm time-processing method